Neuronal and molecular substrates for optimal foraging in Caenorhabditis elegans. - Milward, K; Busch, K; Murphy, R; de Bono, M; Olofsson, B (2011)
Variation in food quality and abundance requires animals to decide whether to stay on a poor food patch or leave in search of better food. An important question in behavioral ecology asks when is it optimal for an animal to leave a food patch it is depleting. Although optimal foraging is central to evolutionary success, the neural and molecular mechanisms underlying it are poorly understood. Here we investigate the neuronal basis for adaptive food-leaving behavior in response to resource depletion in Caenorhabditis elegans, and identify several of the signaling pathways involved. The ASE neurons, previously implicated in salt chemoattraction, promote food-leaving behavior via a cGMP pathway as food becomes limited. High ambient O(2) promotes food-leaving via the O(2)-sensing neurons AQR, PQR, and URX. Ectopic activation of these neurons using channelrhodopsin is sufficient to induce high food-leaving behavior. In contrast, the neuropeptide receptor NPR-1, which regulates social behavior on food, acts in the ASE neurons, the nociceptive ASH neurons, and in the RMG interneuron to repress food-leaving. Finally, we show that neuroendocrine signaling by TGF-β/DAF-7 and neuronal insulin signaling are necessary for adaptive food-leaving behavior. We suggest that animals integrate information about their nutritional state with ambient oxygen and gustatory stimuli to formulate optimal foraging strategies.